Ergebnisse einer Reviewstudie zur Evaluation von Physiklehrbüchern - Jonas-Ahrend, Gabriela; Kapanadze, Marika; Mazzolini, Alexander; Joubran, Fadeel

Assessment of Energy Efficiency and Flexibility Measures in Electrified Process Heat Generation Based on Simulations in the Animal Feed Industry - Knorr, Lukas; Schlosser, Florian; Meschede, Henning (Journal of Sustainable Development of Energy, Water and Environment Systems)
Keywords: Energy Engineering and Power Technology; Water Science and Technology; Environmental Science (miscellaneous); Renewable Energy; Sustainability and the Environment

Feynman-Kac formula for fiber Hamiltonians in the relativistic Nelson model in two spatial dimensions - Hinrichs, Benjamin; Matte, Oliver (arXiv:2309.09005)
In this proceeding we consider a translation invariant Nelson type model in two spatial dimensions modeling a scalar relativistic particle in interaction with a massive radiation field. As is well-known, the corresponding Hamiltonian can be defined with the help of an energy renormalization. First, we review a Feynman-Kac formula for the semigroup generated by this Hamiltonian proven by the authors in a recent preprint (where several matter particles and exterior potentials are treated as well). After that, we employ a few technical key relations and estimates obtained in our preprint to present an otherwise self-contained derivation of new Feynman-Kac formulas for the fiber Hamiltonians attached to fixed total momenta of the translation invariant system. We conclude by inferring an alternative derivation of the Feynman-Kac formula for the full translation invariant Hamiltonian.

A Sub-Threshold Microwave RFID Tag Chip, Compatible With RFID MIMO Reader Technology - Haddadian, Sanaz; Scheytt, J. Christoph; von Bögel, Gerd; Grenter, Thorben (IEEE Journal of Radio Frequency Identification)
We present a fully integrated radio frequency identifications transponder chip operating at 5.8 GHz, which is compatible with the class-1 generation-2 of the Electronic Product Code protocol (EPC-C1 G2). The tag chip including the analog front-end and the digital baseband processor, are designed in the sub-threshold regime (0.5 V) with a total supply current of less than 50 μA. As a power scavenging unit, a single-stage differential-drive rectifier structure is designed and fabricated with standard threshold voltage (SVT) MOS elements in a commercial 65-nm CMOS process, to provide 0.8 V of rectified voltage. Measurements performed on the fabricated single-stage structure show a maximum power conversion efficiency of 69.6% for a 22 kΩ load and a sensitivity of -12.5 dBm, which corresponds to more than 1 m of reading range. The power conversion efficiency at this range is about 64%.

Lessons Learned from the Introduction of Systems Engineering - Wilke, Daria; Grothe, Robin; Bretz, Lukas; Anacker, Harald; Dumitrescu, Roman (Systems)
The introduction of Systems Engineering is an approach for dealing with the increasing complexity of products and their associated product development. Several introduction strategies are available in the literature; nevertheless, the introduction of Systems Engineering into practice still poses a great challenge to companies. Many companies have already gained experience in the introduction of Systems Engineering. Therefore, as part of the SE4OWL research project, the need to conduct a study including expert interviews and to collect the experiences of experts was identified. A total of 78 hypotheses were identified from 13 expert interviews concerning the lessons learned. Using exclusion criteria, 52 hypotheses were validated in a subsequent quantitative survey with 112 participants. Of these 52 hypotheses, 40 could be confirmed based on the survey results. Only four hypotheses were rejected, and eight could neither be confirmed nor rejected. Through this research, guidance is provided to companies to leverage best practices for the introduction of their own Systems Engineering and to avoid the poor practices of other companies.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

Soziotechnische Gestaltung einer intelligenten Personaleinsatzplanung - Gabriel, Stefan; Bentler, Dominik; Bansmann, Michael; Andrew Latos, Benedikt; Kühn, Arno; Dumitrescu, Roman (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract In diesem Beitrag wird die soziotechnische Gestaltung einer Intelligenten Personaleinsatzplanung beim Unternehmen Miele & Cie. KG im Rahmen des Leuchtturmprojekts „InTime“ im Kompetenzzentrum Arbeitswelt.Plus beschrieben. Hierzu werden die Durchführung und Auswertung einer Interviewreihe sowie das daraus erarbeitete Soll-Konzept vorgestellt.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Soziotechnisches Risikomanagement als Erfolgsfaktor für die Digitale Transformation - Menzefricke, Jörn Steffen; Gabriel, Stefan; Gundlach, Thomas; Hobscheidt, Daniela; Kürpick, Christian; Schnasse, Felix; Scholtysik, Michel; Seif, Heiko; Koldewey, Christian; Dumitrescu, Roman (Schwerpunkt Business Model Innovation)

Partizipatives Gestaltungsvorgehen bei der Einführung künstlicher Intelligenz in produzierenden Unternehmen - Bentler, Dominik; Gabriel, Stefan; Latos, Benedikt A.; Dietrich, Oliver; Dumitrescu, Roman; Maier, Günter W. (GfA-Frühjahrskongress 2023)

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Design of individual simulation games in manufacturing companies for game-based learning - Machon, Fabian; Gabriel, Stefan; Latos, Benedikt; Holtkötter, Christoph; Lütkehoff, Ben; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Process Mining Data Canvas: A method to identify data and process knowledge for data collection and preparation in process mining projects - Brock, Jonathan; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Targeted-oriented selection of engineering methods - Wilke, Daria; Schierbaum, Anja; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

On the Membership and Correctness Problem for State Serializability and Value Opacity - König, Jürgen

XCS for Self-awareness in Autonomous Computing Systems - Hansmeier, Tim

Improved Hardness Results for the Guided Local Hamiltonian Problem - Gharibian, Sevag; Hayakawa, Ryu; Gall, François Le; Morimae, Tomoyuki (Proceedings of the 50th EATCS International Colloquium on Automata, Languages and Programming (ICALP))
Estimating the ground state energy of a local Hamiltonian is a central problem in quantum chemistry. In order to further investigate its complexity and the potential of quantum algorithms for quantum chemistry, Gharibian and Le Gall (STOC 2022) recently introduced the guided local Hamiltonian problem (GLH), which is a variant of the local Hamiltonian problem where an approximation of a ground state is given as an additional input. Gharibian and Le Gall showed quantum advantage (more precisely, BQP-completeness) for GLH with $6$-local Hamiltonians when the guiding vector has overlap (inverse-polynomially) close to 1/2 with a ground state. In this paper, we optimally improve both the locality and the overlap parameters: we show that this quantum advantage (BQP-completeness) persists even with 2-local Hamiltonians, and even when the guiding vector has overlap (inverse-polynomially) close to 1 with a ground state. Moreover, we show that the quantum advantage also holds for 2-local physically motivated Hamiltonians on a 2D square lattice. This makes a further step towards establishing practical quantum advantage in quantum chemistry.

Stakeholder-oriented Elaboration of Artificial Intelligence use cases using the example of Special-Purpose engineering - Humpert, Lynn; Wäschle, Moritz; Horstmeyer, Sarah; Anacker, Harald; Dumitrescu, Roman; Albers, Albert (Procedia CIRP)
Keywords: General Medicine

Pseudo-Labeling Machine Learning Algorithm for Predictive Maintenance of Relays - Winkel, Fabian; Wallscheid, Oliver; Scholz, Peter; Böcker, Joachim (IEEE Open Journal of the Industrial Electronics Society)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

Run-to-Failure Relay Dataset for Predictive Maintenance Research With Machine Learning - Winkel, Fabian; Deuse-Kleinsteuber, Johannes; Böcker, Joachim (IEEE Transactions on Reliability)
Keywords: Electrical and Electronic Engineering; Safety; Risk; Reliability and Quality

Neural Networks as Black-Box Benchmark Functions Optimized for Exploratory Landscape Features - Prager, Raphael Patrick; Dietrich, Konstantin; Schneider, Lennart; Schäpermeier, Lennart; Bischl, Bernd; Kerschke, Pascal; Trautmann, Heike; Mersmann, Olaf (Proceedings of the 17th ACM/SIGEVO Conference on Foundations of Genetic Algorithms)
Artificial benchmark functions are commonly used in optimization research because of their ability to rapidly evaluate potential solutions, making them a preferred substitute for real-world problems. However, these benchmark functions have faced criticism for their limited resemblance to real-world problems. In response, recent research has focused on automatically generating new benchmark functions for areas where established test suites are inadequate. These approaches have limitations, such as the difficulty of generating new benchmark functions that exhibit exploratory landscape analysis (ELA) features beyond those of existing benchmarks.The objective of this work is to develop a method for generating benchmark functions for single-objective continuous optimization with user-specified structural properties. Specifically, we aim to demonstrate a proof of concept for a method that uses an ELA feature vector to specify these properties in advance. To achieve this, we begin by generating a random sample of decision space variables and objective values. We then adjust the objective values using CMA-ES until the corresponding features of our new problem match the predefined ELA features within a specified threshold. By iteratively transforming the landscape in this way, we ensure that the resulting function exhibits the desired properties. To create the final function, we use the resulting point cloud as training data for a simple neural network that produces a function exhibiting the target ELA features. We demonstrate the effectiveness of this approach by replicating the existing functions of the well-known BBOB suite and creating new functions with ELA feature values that are not present in BBOB.
Keywords: Benchmarking; Instance Generator; Black-Box Continuous Optimization; Exploratory Landscape Analysis; Neural Networks

Nullifying the Inherent Bias of Non-invariant Exploratory Landscape Analysis Features - Prager, Raphael Patrick; Trautmann, Heike (Applications of Evolutionary Computation)
Exploratory landscape analysis (ELA) in single-objective black-box optimization relies on a comprehensive and large set of numerical features characterizing problem instances. Those foster problem understanding and serve as basis for constructing automated algorithm selection models choosing the best suited algorithm for a problem at hand based on the aforementioned features computed prior to optimization. This work specifically points to the sensitivity of a substantial proportion of these features to absolute objective values, i.e., we observe a lack of shift and scale invariance. We show that this unfortunately induces bias within automated algorithm selection models, an overfitting to specific benchmark problem sets used for training and thereby hinders generalization capabilities to unseen problems. We tackle these issues by presenting an appropriate objective normalization to be used prior to ELA feature computation and empirically illustrate the respective effectiveness focusing on the BBOB benchmark set.

Peak-A-Boo! Generating Multi-objective Multiple Peaks Benchmark Problems with Precise Pareto Sets - Schäpermeier, Lennart; Kerschke, Pascal; Grimme, Christian; Trautmann, Heike (Evolutionary Multi-Criterion Optimization)
The design and choice of benchmark suites are ongoing topics of discussion in the multi-objective optimization community. Some suites provide a good understanding of their Pareto sets and fronts, such as the well-known DTLZ and ZDT problems. However, they lack diversity in their landscape properties and do not provide a mechanism for creating multiple distinct problem instances. Other suites, like bi-objective BBOB, possess diverse and challenging landscape properties, but their optima are not well understood and can only be approximated empirically without any guarantees.

Pflacco: Feature-Based Landscape Analysis of Continuous and Constrained Optimization Problems in Python - Prager, Raphael Patrick; Trautmann, Heike (Evolutionary Computation)
The herein proposed Python package pflacco provides a set of numerical features to characterize single-objective continuous and constrained optimization problems. Thereby, pflacco addresses two major challenges in the area optimization. Firstly, it provides the means to develop an understanding of a given problem instance, which is crucial for designing, selecting, or configuring optimization algorithms in general. Secondly, these numerical features can be utilized in the research streams of automated algorithm selection and configuration. While the majority of these landscape features is already available in the R package flacco, our Python implementation offers these tools to an even wider audience and thereby promotes research interests and novel avenues in the area of optimization.

Privacy-Preserving Natural Language Processing - Habernal, Ivan; Mireshghallah, Fatemehsadat; Thaine, Patricia; Ghanavati, Sepideh; Feyisetan, Oluwaseyi (Proceedings of the 17th Conference of the European Chapter of the Association for Computational Linguistics: Tutorial Abstracts)

Trade-Offs Between Fairness and Privacy in Language Modeling - Matzken, Cleo; Eger, Steffen; Habernal, Ivan (Findings of the Association for Computational Linguistics: ACL 2023)

Crowdsourcing on Sensitive Data with Privacy-Preserving Text Rewriting - Mouhammad, Nina; Daxenberger, Johannes; Schiller, Benjamin; Habernal, Ivan (Proceedings of the 17th Linguistic Annotation Workshop (LAW-XVII))

Privacy-Preserving Models for Legal Natural Language Processing - Yin, Ying; Habernal, Ivan (Proceedings of the Natural Legal Language Processing Workshop 2022)

An Optimized Third-Harmonic Injection Reduces DC-Link Voltage Ripple in Cascaded H-Bridge Converters up to 50% for all Power Factors - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (2023 25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe))
Star-connected cascaded H-bridge Converters require large DC-link capacitors to buffer the second-order harmonic voltage ripple. First, it is analytically proven that the DC-link voltage ripple is proportional to the apparent converter power and does not depend on the power factor for nominal operation with sinusoidal reference arm voltages and currents. A third-harmonic zero-sequence voltage injection with an optimal amplitude and phase angle transforms the 2nd harmonic to a 4th harmonic DC-link voltage ripple. This reduces the voltage ripple by exactly 50% for all power factors at steady-state at balanced conditions. However, this requires 54% additional modules for unity power factor operation and even 100% for pure reactive power operation to account for the increased reference arm voltages due to the large amplitude of the optimal third-harmonic injection. If not enough modules are available, an adaptive discontinuous PWM is utilized to still minimize the voltage ripple for the given number of modules and power factor. With a very limited number of modules (modulation index is 1.15), the proposed method still reduces the DC-link voltage ripple by 24.4% for unity power factor operation. It requires the same number of modules as the commonly utilized 3rd harmonic injection with 1/6 of the grid voltage amplitude and achieves superior results. Simulations of a 10 kV/1 MVA system confirm the analysis.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Capacitor voltage ripple; Zero sequence voltage; Third harmonic injection

Fade-Over Strategy for use of Model Predictive Direct Self-Control with Field-Oriented Control - Pena, Mario; Meyer, Michael; Wallscheid, Oliver; Böcker, Joachim (2023 IEEE International Electric Machines and Drives Conference (IEMDC))

Zuweisung verteilter Speicher unter Maximierung der minimalen gewichteten Bandbreite - Decking, Leo
Bei dem betrachteten Speicherproblem werden Daten mit verschiedenen Zugriffswahrscheinlichkeiten auf Speicher mit verschiedenen Bandbreiten und Kapazitäten aufgeteilt, dabei sind Replikate erlaubt. Es wird die nach Zugriffswahrscheinlichkeit gewichtete kleinste Bandbreite der Daten maximiert. Wir zeigen, dass sowohl das diskrete Speicherproblem, bei dem die Bandbreite der Speicher jeweils gleichmäßig auf die dort abgelegten Daten aufgeteilt wird, als auch das kontinuierliche Speicherproblem, bei dem die Bandbreite der Speicher beliebig auf abgelegte Daten verteilt werden darf, NP-schwer ist. Es können also, wenn P ̸ = NP, keine effizienten Algorithmen für eine optimale Lösung existieren. Stattdessen zeigen wir jeweils einen 1/2-Approximationsalgorithmus.

On the Integration of Sampling Rate Synchronization and Acoustic Beamforming - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (European Signal Processing Conference (EUSIPCO))

Digitizing Processes in Manufacturing Companies via Low-Code Software (to appear) - Weidmann, Nils; Kirchhoff, Jonas; Sauer, Stefan
Low-code development platforms (LCDPs) recently sparked interest in both academia and industry, promising to speed up software development and make it accessible to users with little or no programming experience. Thus, the mass-development of software applications that are custom-made to the tasks, skills, and preferences of end users is potentially enabled. Although different LCDPs have been analysed with respect to their functionality and applied to exemplary case studies in recent work, there is a shortage of experience reports in which LCDPs are used to digitize business processes in small and medium manufacturing enterprises. In this paper, we therefore summarize our experience from supporting industry partners to identify business processes that are suitable for being implemented with low-code technologies and to select an LCDP that meets the requirements of the business process while aligning with the overall digitization strategy of the respective company. We also present the opportunities and challenges of the low-code approach as perceived by industry partners. In summary, the low-code approach should be seen as an essential factor for the digitization of business processes in small and medium manufacturing companies.

Knowledge Transfer Concepts for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Temmen, Katrin; Bode, Henrik (2023 IEEE Global Engineering Education Conference (EDUCON))

Introduction to the Minitrack on Data-driven Services in Manufacturing: Innovation, Engineering, Transformation, and Management - Koldewey, Christian; Martin, Rabe; Dumitrescu, Roman; Winter, Johannes (Proceedings of the 56th Hawaii International Conference on System Sciences)

Datengestützte Produktplanung
Unter dem Einfluss der Digitalisierung wandeln sich mechatronische Produkte zunehmend in cyber-physische Systeme (CPS). Diese sind in der Lage, umfangreiche Daten während ihres Betriebs zu sammeln und über digitale Netzinfrastrukturen zur Verfügung zu stellen. Gemeinsam mit weiteren Daten aus der Betriebsphase versprechen sie wertvolle Erkenntnisse über das Produkt und dessen Nutzer, welche für die Hersteller der CPS insbesondere für die Planung zukünftiger Produktgenerationenrelevant sind. Die zielgerichtete Nutzung von Betriebsdaten in der strategischen Produktplanung stellt produzierende Unternehmen jedoch noch vor zahlreiche Herausforderungen, z. B. hinsichtlich der Identifizierung Erfolg versprechender Use Cases. Das vorliegende Buch greift diese Herausforderungen auf und stellt ein Instrumentarium vor, das produzierende Unternehmen zur datengestützten Produktplanung befähigt. Neben der Vorstellung praxiserprobter Methoden und Werkzeuge werden Einblicke in vier Pilotprojekte gegeben. Das Instrumentarium entstand im Forschungsprojekt „DizRuPt“, das vom Bundesministerium für Bildung und Forschung (BMBF) gefördert wurde.

Application-based learning of signal analysis methods with the help of a graphical open-source software - Hetkämper, Tim; Koch, Kevin; Webersen, Manuel; Claes, Leander (SEFI 51th Annual Conference Proceedings - Engineering Education for Sustainability)

Frame-Wise and Overlap-Robust Speaker Embeddings for Meeting Diarization - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

LibriWASN: A Data Set for Meeting Separation, Diarization, and Recognition with Asynchronous Recording Devices - Schmalenstroeer, Joerg; Gburrek, Tobias; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)

A Teacher-Student Approach for Extracting Informative Speaker Embeddings From Speech Mixtures - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (INTERSPEECH 2023)

"Always Contribute Back": A Qualitative Study on Security Challenges of the Open Source Supply Chain - Wermke, Dominik; Klemmer, Jan H.; Wöhler, Noah; Schmüser, Juliane; Sri Ramulu, Harshini; Acar, Yasemin; Fahl, Sascha (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

Pushed by Accident: A Mixed-Methods Study on Strategies of Handling Secret Information in Source Code Repositories - Krause, Alexander; Klemmer, Jan H.; Huaman, Nicolas; Wermke, Dominik; Acar, Yasemin; Fahl, Sascha (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023)

It’s like flossing your teeth: On the Importance and Challenges of Reproducible Builds for Software Supply Chain Security - Fourné, Marcel; Wermke, Dominik; Enck, William; Fahl, Sascha; Acar, Yasemin (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

"In Eighty Percent of the Cases, I Select the Password for Them": Security and Privacy Challenges, Advice, and Opportunities at Cybercafes in Kenya - Munyendo, Collins W.; Acar, Yasemin; Aviv, Adam J. (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

Ethical Frameworks and Computer Security Trolley Problems: Foundations for Conversations - Kohno, Tadayoshi; Acar, Yasemin; Loh, Wulf (CoRR)

A World Full of Privacy and Security (Mis)conceptions? Findings of a Representative Survey in 12 Countries - Herbert, Franziska; Becker, Steffen; Schaewitz, Leonie; Hielscher, Jonas; Kowalewski, Marvin; Sasse, M. Angela; Acar, Yasemin; Dürmuth, Markus (Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems, CHI 2023, Hamburg, Germany, April 23-28, 2023)

"We are a startup to the core": A qualitative interview study on the security and privacy development practices in Turkish software startups - Keküllüoglu, Dilara; Acar, Yasemin (44th IEEE Symposium on Security and Privacy, SP 2023, San Francisco, CA, USA, May 21-25, 2023)

"Oh yes! over-preparing for meetings is my jam :)": The Gendered Experiences of System Administrators - Kaur, Mannat; Sri Ramulu, Harshini; Acar, Yasemin; Fiebig, Tobias (Proc. ACM Hum. Comput. Interact.)

S3C2 Summit 2202-09: Industry Secure Suppy Chain Summit - Tran, Mindy; Acar, Yasemin; Cucker, Michel; Enck, William; Kapravelos, Alexandros; Kästner, Christian; Williams, Laurie A. (CoRR)

S3C2 Summit 2023-02: Industry Secure Supply Chain Summit - Dunlap, Trevor; Acar, Yasemin; Cucker, Michel; Enck, William; Kapravelos, Alexandros; Kästner, Christian; Williams, Laurie A. (CoRR)

S3C2 Summit 2023-06: Government Secure Supply Chain Summit - Enck, William; Acar, Yasemin; Cukier, Michel; Kapravelos, Alexandros; Kästner, Christian; Williams, Laurie A. (CoRR)

"Security is not my field, I’m a stats guy": A Qualitative Root Cause Analysis of Barriers to Adversarial Machine Learning Defenses in Industry - Mink, Jaron; Kaur, Harjot; Schmüser, Juliane; Fahl, Sascha; Acar, Yasemin (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023)